KAJIAN BENTUK DAN FUNGSI WANDA WAYANG KULIT PURWA GAYA SURAKARTA, KAITANNYA DENGAN PERTUNJUKAN - Bambang Suwarno; Timbul Haryono; R.M. Soedarsono; S Soetarno (Gelar : Jurnal Seni Budaya, 2014)
ABSTRACTThe writing is part of the writer’s discussion about the dissertation research as part of his doctoral programfinal examination. Focus of the study is wanda of wayang kulit purwa of Surakarta style, its function in the fifthpakeliran (wayang performance), and its relationship with sanggit lakon (story treatment). In solving theproblem, the writer uses the approach of pedalangan (puppetry) aesthetics completed by phenomenology,psychology, and creativity approaches in holistic thinking as the instrument of data analysis.Keywords: form, function, wanda, wayang kulit purwa, performance